Penerapan listrik tenaga surya sebagai sumber pengereman motor induksi 3 phasa - Berlianti, Berlianti (Jurnal Momentum ISSN 1693-752X)
Dynamic breaking is one of the applying method on the three phase induction motor breaking system. An advantage of dynamic breaking system is its simplicity controlling dynamic breaking speed and decreasing mechanical losses. Obviously it was needed direct current power supply for breaking. Lack of the electrical supply can adopt from electrical energy that generated from solar energy. The performance parameter obtained by using contactor to feed the breaking supply on three phase induction motor and controlling breaking current gradually. The value will be breaking current as the function of breaking time; breaking current as the function of  breaking power; breaking current as the function of breaking Torque.From the experiment of dynamic breaking system on 3 phase squierrel cage induction motor, 1 kW, Y connection, 380V, 2.7 A, 50 Hz it was found that the breaking time average from solar panel is 1.6 second at dc voltage level 19 Volt, 1.72 second at 17 Volt, 2.77 second at 15.3 Volt, 3.03 at 14.3 Volt . It is 7.44 second with no breaking system.It describes that the higher the dc voltage level is aplied to the dynamic breaking system, the faster breaking time is achieved The increasing voltage level will cause to increase electric current value of breaking. It sequences to increase the breaking electric power and breaking torque reciprocally.